HUBUNGAN ANTARA KEMANDIRIAN BELAJAR DAN LINGKUNGAN BELAJAR DI SEKOLAH TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN SEKECAMATAN KLIRONG TAHUN AJARAN 2021/2022 - Nur Isnaeni; Tri Saptuti Susiani; Muhamad Chamdani (caXra: Jurnal Pendidikan Sekolah Dasar, 2022)
The study aims to analyze correlation of: (1) independence in learning on natural science learning outcomes, (2) learning environment at schools on natural science learning outcomes, and (3) independence in learning and learning environment at schools on natural science learning outcomes to fifth grade students of public elementary schools. It was multiple correlation quantitative method. The population were 725 students with a sample of 312 students who were randomly selected with cluster random sampling technique. The results indicated that: (1) there was positive and significant correlation between independence in learning and natural science learning outcomes (Sig. 0.000 < 0.05) with coefficient value 0.461; (2) there was positive and significant correlation between learning environment at schools and natural science learning outcomes (Sig. 0.000 < 0.05) with coefficient value 0.446; and (3) there was positive and significant correlation between independence in learning and learning environment at schools on natural science learning outcomes (Sig. 0.000 < 0.05) with coefficient value 0.488. It concludes that there is positive and significant correlation of the independence in learning and learning environment at schools on natural science learning outcomes to fifth grade students of public elementary schools.